NORMAL ANORECTAL MRI ANATOMY FOR RECTAL CANCERS - Cendikiawan, Albert; Christina, Natalia Maria (International Journal of Radiology and Imaging, 2026)
Magnetic resonance imaging plays an important role in evaluation and management of rectal cancer. The rectum starts from the sigmoid take-off and ends at the anorectal ring. The anal canal starts from the anorectal ring and ends at the anal verge. The rectum is enveloped by the mesorectum and mesorectal fascia, both of which are critical for oncologic staging and surgical planning. The rectum includes both intraperitoneal and extraperitoneal segments. The rectal vascularization is provided by superior rectal artery, and its venous drainage by the portal venous system and the systemic circulation. Lymphatic drainage involves multiple nodal groups, classified as regional and non-regional. A comprehensive understanding of these anatomical features is essential for accurate staging, optimal treatment planning, and improved outcomes in rectal cancer management.